Functional trait scaling relationships across 13 temperate mosses growing in wintertime. Issue 4 (3rd May 2014) - Wang, Zhe; Bao, Weikai; Feng, Defeng; Lin, Honghui
Abstract: Mosses growing in wintertime exert important ecosystem function, but we know little about their fundamental functional trait levels and scaling relationships across species. Thus the present study chose 13 common mosses growing under a temperate deciduous forest in wintertime to measure their light‐saturated assimilation rate (Amass ), dark respiration rate (Rdmass ), major element concentrations and stoichiometric ratios (Cmass, Nmass, Pmass, C:P, C:P and N:P) and the shoot mass per area (SMA). Their bivariate log–log scaling relationships were determined by standardized major axes approach. We confirmed that except Cmass, the nutrient concentrations and metabolic rates of our mosses were higher than that of mosses growing at warmer sites but the SMA was lower than for Sphagnum species. Furthermore, the functional trait levels were totally lower than those of vascular plant leaves except Pmass . Besides, we found the Nmass and Pmass were significantly positively related to Amass and Rdmass but negatively associated with SMA. The C:P and N:P were also closely linked with Amass, Rdmass and SMA. The SMA was significantly related to Rdmass but not to Amass . Functional trait relationships across the current species deviated from previous studies of mosses but were generally analogous to those of vascular plant leaves only with different scaling. The findings suggest that mosses allocated a greater proportion of nutrients to metabolic components rather than to the non‐photosynthetic tissues. In addition, phosphorus was associated more closely with other functional traits than was nitrogen and might play a greater role to withstand the cold temperatures in wintertime for mosses.